flavouring with Olive oil - Gordon-Smith, Clare (Philadelphia : Courage Books, 1996)
Thirty quick and easy recipes using olive oil in marinades, appetizers, salads, entrees, and something sweet.
Includes index.
All Ages.
Keywords: Cookery (Olive oil).; Olive oil